Globalisation, market economy and human security: The Indian experience - Jain, R.B. (1996)
Providing briefly the salient features of globalisation-driven package of economic reforms in India with its background, the author attempts analytically to evaluate its impact on socio-economic aspects of our economy during 1991-96 with particular emphasis on the critical social parameters - like poverty, unemployment, etc. - with a future perspective on realising competitiveness with human security. - Reproduced
Keywords: Globalization - India; Economic and social development; Globalization